A Randomized Controlled Trial Investigating Online Training for Prelinguistic Communication - Feuerstein, Julie L. (J Speech Lang Hear Res, 2020)
PURPOSE: This study explored the utility of online training as a platform for teaching early intervention speech-language pathologists to recognize potentially communicative, prelinguistic behaviors in young children with physical disabilities and complex communication needs. METHOD: Using a randomized controlled trial, 45 early intervention speech-language pathologists were randomly assigned to one of three conditions within an online training: practice with implicit problem-solving (identification condition), practice with explicit problem-solving (reflection condition), or no practice (control condition). Knowledge about early communication, skill at recognizing prelinguistic behaviors, time taken to complete the training, and perceptions of the training experience were examined. RESULTS: Participants in the no-practice control condition took significantly less time to complete the training, achieved the same positive outcomes on the knowledge and skill assessments, and rated the training as appealing as compared with participants assigned to the more time-intensive identification and reflection practice conditions. CONCLUSIONS: Results suggest the importance of considering efficiency and appeal when designing successful trainings for moving evidence into practice.